1976
DOI: 10.1136/ard.35.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Nervous system involvement in systemic lupus erythematosus

Abstract: . (1976). Annals of the Rheumatic Diseases, 35,[398][399][400][401][402][403][404][405][406]. Nervous system involvement in systemic lupus erythematosus. In a retrospective analysis of 80 patients with systemic lupus erythematosus (SLE) seen over a 10-year period, 41 (51 %) exhibited neurological manifestations. Nervous system involvement was characterized by a significantly greater involvement of black patients (P < 0 02), a higher incidence of renal failure after the first appearance of neurological features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
2
8

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(85 citation statements)
references
References 28 publications
3
72
2
8
Order By: Relevance
“…Other disorders that could produce hemiparesis (i.e., cerebral abscess) were present in some of the patients. 31 For these reasons and because some studies included only SLE patients with "neuropsychiatric manifestations," the frequency of stroke in SLE cannot be determined from these studies. A higher frequency of strokes is reported in autopsy studies 57 -20 and would not be expected to represent the frequency of stroke in the general SLE population.…”
Section: Discussionmentioning
confidence: 99%
“…Other disorders that could produce hemiparesis (i.e., cerebral abscess) were present in some of the patients. 31 For these reasons and because some studies included only SLE patients with "neuropsychiatric manifestations," the frequency of stroke in SLE cannot be determined from these studies. A higher frequency of strokes is reported in autopsy studies 57 -20 and would not be expected to represent the frequency of stroke in the general SLE population.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychiatric involvement in systemic lupus erythematosus (NPSLE) is a serious complication of the disease (1,2). Bluestein et al demonstrated that IgG antineuronal antibodies (anti-N) were present in much higher concentrations in the cerebrospinal fluid (CSF) of patients with active NPSLE than in the CSF of SLE patients without active neuropsychiatric manifestations (3).…”
mentioning
confidence: 99%
“…It is important to realize that vasculitis is rare in SLE and that most vascular complications are related to thrombosis [219,220]. The absence of vasculitic changes is particularly striking in NPSLE [221].…”
Section: Neuropsychiatric Systemic Lupus Erythematosismentioning
confidence: 99%